The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.fuel.2020.117991
|View full text |Cite
|
Sign up to set email alerts
|

Use of waste vegetable oil for hydrotreated vegetable oil production with high-temperature electrolysis as hydrogen source

Abstract: The research of renewable alternatives to decarbonize the transport sector and to reduce the consumption of fossil fuels pushes towards the development of more sustainable solutions for fuel production. Among the diesel substitutes, hydrotreated vegetable oil (HVO) is considered one of the most promising options, since it can be blended with fossil diesel without limitations. In this context, this paper assesses the technical and economic feasibility of producing HVO using waste vegetable oil (WVO) as feedstoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The fact that 'gray H 2 ' accumulates significant environmental impacts along its production chain, which are transferred to the products that use it, associated with a movement to unlink the petrochemical sector, intensified the search for solutions capable of obtaining hydrogen from less aggressive routes. Water electrolysis is one of the most promising options of this new generation of technologies [2], mainly when the energy demand of the process is supplied by a predominantly renewable grid such as the existing in Brazil [42]. This circumstance meant that the study also examined such an alternative for obtaining bioLPG.…”
Section: Scenarios Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that 'gray H 2 ' accumulates significant environmental impacts along its production chain, which are transferred to the products that use it, associated with a movement to unlink the petrochemical sector, intensified the search for solutions capable of obtaining hydrogen from less aggressive routes. Water electrolysis is one of the most promising options of this new generation of technologies [2], mainly when the energy demand of the process is supplied by a predominantly renewable grid such as the existing in Brazil [42]. This circumstance meant that the study also examined such an alternative for obtaining bioLPG.…”
Section: Scenarios Definitionmentioning
confidence: 99%
“…Liquefied Petroleum Gas (LPG), a fuel mixture mainly composed of propane and butane at varied proportions [1], also has the potential to join this group, becoming partially renewable if produced from feedstocks such as vegetable oils, biomass, and oleaginous residues. A technologically established way for this to occur is the hydrotreatment of vegetable oils (HVO) route, which consists of hydrogenating the triglycerides present in that raw vegetable material [2]. If conducted under controlled temperature and pressure conditions, the process generates both HVO biodiesel (also called 'green' diesel) as the main product and biopropane (bioLPG) as a co-product.…”
Section: Introductionmentioning
confidence: 99%
“…Green diesel produced by hydrotreated vegetable oil (HVO) has better incorporation property with fossil fuel and large amount of waste is recycled by this process which makes it more viable. This process avoids the need of land filling or input of sewage system (Lorenzi et al 2020). Another possibility of green diesel use is related with the concern of global warming.…”
Section: Future Aspects Of Green Dieselmentioning
confidence: 99%
“…According to Statista Research Department, vegetable oils worldwide amounted to 203.91 million tons in 2019/2020. The main challenges for using these vegetable oil wastes are associated with their collection and treatment 5 . A study conducted by Liu et al showed the lack of economic incentives, disposal regulation policies, and the lack of collection awareness to reuse cooking oil waste 6…”
Section: Introductionmentioning
confidence: 99%
“…Among various vegetable cooking oil reuse alternatives, biodiesel production is highlighted, avoiding using virgin vegetable oils and allowing the circular economy concept 5 . According to Tsai, in cities like Taiwan, cooking vegetable oil recycling is mandatory and involves commercial and residential sectors 7 .…”
Section: Introductionmentioning
confidence: 99%